Creative Arts, Recreational Activities, and Free Play as Correlates of Creative Skills Development Among Primary School Pupils - Imaobong Essien; Victor M. Alasa (Jurnal Pendidikan Abad Ke-21, 2025)
This study examined exposure to creative arts, recreational activities, and free play as correlates of creative skills development among primary school pupils in Uyo metropolis of Akwa Ibom State, Nigeria. The study adopted the correlational survey research design. The population of the study comprised all primary two pupils. The sample for this study consisted of 500 primary two pupils. The study adopted the multistage random sampling technique to draw samples for the study. The instrument used for data collection was designed by the researchers and named Creative Arts, Recreational Activities, Free Play, and Creative Skills Development Questionnaire (CARAFPCSDQ). The instrument was pilot tested for reliability with an index of 0.81. Three research questions were asked, and three hypotheses tested at 0.05, level of significance. Data collected were analyzed using descriptive statistics of frequency count and simple percentage to answer research questions while Pearson Product Moment Correlation (PPMC) was used to test the hypotheses at 0.05, level of significance. The results showed that primary school pupils are exposed to creative arts, recreational activities, and free play. The result also showed a significant relationship between exposure to creative arts, free play, and creative skills development among primary school pupils. The study, however, found no significant relationship between recreational activities and creative skills development of primary school pupils. Based on the findings of the study, recommendations were made among which are, government should train and post more creative arts teachers to schools. Parents and teachers should create more time and an enabling environment for pupils to engage in free play at home and in school.